2001
DOI: 10.1080/17476930108815418
|View full text |Cite
|
Sign up to set email alerts
|

Universal meromorphic functions

Abstract: Using the techniques of the hypercyclicity criterion, we prove that there is a meromorphic function f ( z ) on the complex plane whose translates f(z + n) for all n 1 1, are dense in the metric space of meromorphic functions on any region in the plane. In addition, we prove the analogue of the result for non-Euclidean translation on the unit disk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In Theorem 2.1 below, we construct a universal element without the assumption that the semigroup X is a topological semigroup, nor the assumption that X possess an identity element. Then in Corollary 2.2, we show how those two assumptions reduce Theorem 2.1 to the format of the universality criterion obtained in [6] and [23].…”
Section: Main Results and Outline Of Dissertationmentioning
confidence: 86%
See 1 more Smart Citation
“…In Theorem 2.1 below, we construct a universal element without the assumption that the semigroup X is a topological semigroup, nor the assumption that X possess an identity element. Then in Corollary 2.2, we show how those two assumptions reduce Theorem 2.1 to the format of the universality criterion obtained in [6] and [23].…”
Section: Main Results and Outline Of Dissertationmentioning
confidence: 86%
“…In this section we construct a universal element in a separable, complete, metrizable topological semigroup X for a sequence of continuous homomorphisms on X satisfying the well-known universality criterion which was first obtained by Chan [6] and later by Moothathu [23].…”
Section: Main Results and Outline Of Dissertationmentioning
confidence: 99%
“…Lastly, we conclude our discussion with some other universality results for C(R) and L 1 (R). In this section we construct a universal element in a separable, complete, metrizable topological semigroup X for a sequence of continuous homomorphisms on X satisfying the well-known universality criterion which was first obtained by Chan [6] and later by Moothathu [23].…”
Section: Main Results and Outline Of Dissertationmentioning
confidence: 99%
“…The final result of this section is concerned with universal locally univalent meromorphic functions. Chan [8] has shown that there exists a meromorphic function f ∈ M(C) such that the set T f := {f (· + n) : n ∈ N} is dense in M(Ω) for every domain Ω ⊆ C.…”
Section: Universal Locally Univalent Functionsmentioning
confidence: 99%
“…(3) (Universal meromorphic functions) There are Birkhoff-type universality results for meromorphic functions (see e.g. [8]).…”
Section: Introductionmentioning
confidence: 99%